Estudo longitudinal do perfil oxidativo em gestantes saudáveis e com complicações gestacionais - Lucca, Leidiane de (2019)
During gestation, even though it is a physiological process, there is oxidative stress due to a greater metabolic demand and an increase in tissue oxygen consumption, especially in the placenta, in response to fetal growth and maternal physiological changes. Oxidative stress can be evaluated by the relationship between free radicals and antioxidants produced by the body. Excessive production of free radicals has detrimental effects, such as changes in tissue proteins, DNA damage, enzymes and carbohydrates, peroxidation of membrane lipids, among others. The sulfhydryl delta-aminolevulinate dehydratase enzyme (δ-ALA-D) may be inhibited in pro-oxidant situations and this inhibition results in the accumulation of 5-aminolevulinic acid, being directly related to an increase in the production of free radicals. Considering that oxidative stress is directly involved in the physiology of pregnancy, where mainly the placenta is susceptible to damage, thus favoring the development of gestational diseases such as gestational hypertension, preeclampsia and Gestational Diabetes Mellitus. The aim of this study was to evaluate the oxidative profile and activity of the δ-ALA-D enzyme throughout the three trimesters of pregnancy, besides to compare the oxidative profile between pregnant women with and without gestational complications. Oxidative damage parameters were analyzed by quantifying thiobarbituric acid reactive species (TBARS) and nitric oxide (NOx). The antioxidant system evaluation was performed by quantifying protein (P-SH) and non-protein (NP-SH) thiols groups, vitamin C levels, total antioxidant capacity (TAC), plasma iron reduction ability (FRAP), besides determining the activity of the enzymes catalase and δ-ALA-D in pregnant women. According to the results obtained in the present study, the oxidative profile seems to be altered mainly in the second gestational trimester, with an increase in oxidative damage markers and a decrease in antioxidants when compared to the first and third gestational trimester. In addition, oxidative damage markers were significantly higher in pregnant women with gestational complications, while their antioxidant system appears to be decreased due to reduced levels of P-SH, NP-SH, vitamin C, TAC and FRAP, besides decreased activity of catalase and δ-ALA-D enzymes. Because of this, we can conclude that there is a different oxidative response profile in each gestational trimester, as well as an increase in oxidative stress, a decrease in antioxidants and δ- ALA-D activity in pregnant women with complications compared to healthy pregnant women. This may be related to the aggravation of gestational diseases and the evaluation of δ-ALA-D activity may be useful in monitoring the damage during pregnancy because it is an indirect marker of oxidative stress.